The fracking at the crossroads: A technology that advances between economic profitability and environmental sustainability - Dias, Rodrigo Javier (2019)
The global expansion of capitalism has transformed, from the industrial revolutions of the eighteenth and nineteenth centuries, the logics of extraction, production and marketing of goods. With the arrival of neoliberalism and with the objective of maximizing profits and the accumulation of capital, the rhythms of the productive model have accelerated until putting in a close horizon the definitive exhaustion of resources. In this sense, the need to maintain constant supply of products to the market has fostered the research and development of new technologies, which become essential for the exploitation of strategic natural resources, consolidating a neoextractivism that is ravaging the peripheral economies. In recent years, hydraulic fracturing or fracking has become the most widely used technique for the extraction of hydrocarbons in so-called unconventional deposits. However, the environmental impacts and collateral damage generated by the activity put this technology at a crossroads: in South America, exploitation through hydraulic fracturing is legitimized from the States as a synonym of growth, but at the same time its development is not known type of pre-existing organization on the affected territories. Protected areas, natural reserves or communities of native peoples are being absorbed and damaged by the advancement of this technique. That is why the present work raises two questions of difficult answer: what is the true cost of fracking? What is necessary to prioritize, economic profitability or environmental sustainability?